A study of mucormycosis in second wave of COVID-19 - H.T. Lathadevi; T. Shashi Kumar; Ravindra Karadi; Sharanabasappa R. Malipatil; Venkatesh Patil; Shanmukh Kamath (Al Ameen Medical College, 2024)
Background: During the second wave of Covid 19 infection in India, we witnessed a pandemic within an epidemic - that of mucormycosis in Covid-19. Hence, we performed a study on the patients admitted under our care. Objectives: To study the risk factors and clinical presentations of Covid 19 associated mucormycosis; and to know the treatment outcome. Methods: 112 patients with clinical diagnosis of mucormycosis were subjected to diagnostic nasal endoscopy (DNE) and KOH mount. This was followed by contrast MRI and estimation of HbA1c, and levels of various inflammatory markers - D-dimer, LDH, serum ferritin, IL-6 and CRP. All underwent endoscopic/ external clearance of disease with anti-fungal therapy. Patients were followed up for 3 months. Results: The common presenting complaints were headache and facial pain. DNE showed unhealthy mucosa with blackish discoloration of septum or turbinate, mucopurulent discharge, and crusting. 23 patients had palatal involvement; 24 patients had orbital involvement of whom 13 had complete loss of vision during the course of the disease. 63 of the patients had poor glycemic control, with HbA1c >10. Levels of inflammatory markers were all elevated. Maxillary and ethmoid sinuses were most commonly affected sinuses, with intracranial involvement in 18 patients as per MRI. Revision surgery was required in 12 patients.The mortality rate in our study was 8%. Conclusion: Covid associated mucormycosis is a fulminating disease which requires immediate diagnosis and emergent management with both medical and surgical modalities without which patient has high morbidity and mortality.